(untitled) (Global Journal of Human-Social Science, 2013)
The centrality of lexis has been a prominent issue in lexical studies in second language learning Richards 1976 Ard and Gass 1987 Willis 1990 Clark 1993 Coady and Huckin 1997 This research article aims to shed light on understanding vocabulary in a different perspective by examining the nature of vocabulary through the observation of the verb pour in corpus citations The results indicate that a large part of the grammatical aspect is lexically related The corpus citations display the properties of the verb pour that include its various senses of meaning syntactic structures it can fill in typical subjects and objects they co-occur with and argument structures These properties generally determine the verb meaning and how it should appear in sentences and collocate with other words and at the same time distinguish from other verbs behaviour This corpus-based study confirms the unique complexity of the verb lexicon The acquisition of lexicon is then the competence that includes the knowledge of the lexical properties For a learner it would imply that the encoded structural aspects should be learned as an integral part of learning vocabulary Hence it would render the teaching of grammar to some extent redundant